2015
DOI: 10.1039/c5ra13048d
|View full text |Cite
|
Sign up to set email alerts
|

Surface-dependence of interfacial binding strength between zinc oxide and graphene

Abstract: There is an increasing interest in hybrid materials with impacts such as improving structural integrity of known and commonly used materials. Recent experiments have suggested that the adhesion of zinc oxide (ZnO) nanowires with carbon fibers can significantly improve interfacial shear and tensile strength of fiber reinforced polymer composites. We have carried out a systematic study of the interaction between ZnO and graphene based on density functional theory, with a focus on the effect of the surface orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…For pristine graphene, the interaction can be attributed to electrostatic and van der Waals interactions. There is very little charge transfer and deformation in graphene, and the calculated binding strength (1.02 eV) is in good agreement with previous studies . In the cases of O and N doping, the interaction strength of ZnO with the defective graphene increases slightly, whereas for B and Be doping, the interaction strengths are 1.59 and 1.72 eV, respectively, much higher than in the pristine case.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…For pristine graphene, the interaction can be attributed to electrostatic and van der Waals interactions. There is very little charge transfer and deformation in graphene, and the calculated binding strength (1.02 eV) is in good agreement with previous studies . In the cases of O and N doping, the interaction strength of ZnO with the defective graphene increases slightly, whereas for B and Be doping, the interaction strengths are 1.59 and 1.72 eV, respectively, much higher than in the pristine case.…”
Section: Resultssupporting
confidence: 88%
“…There is very little charge transfer and deformation in graphene, and the calculated binding strength (1.02 eV) is in good agreement with previous studies. 44 In the cases of O and N doping, the interaction strength of ZnO with the defective graphene increases slightly, whereas for B and Be doping, the interaction strengths are 1.59 and 1.72 eV, respectively, much higher than in the pristine case. This is primarily due to the electric dipole generated by the positive p-doping center and the extra negative charge on ZnO.…”
Section: Computational Model and Methodsmentioning
confidence: 93%
“…29 The electronegativity of the O-terminated (0001) surface with the exposed O atom layer is much stronger than the (11̅ 00) plane terminated by a stacking sequence of O and Zn layers for the large difference in the electronegativity of Zn (1.65) and O (3.44). 30 Recent computational work indicated that the adsorption of *CO 2 was highly sensitive to the presence of a surface charge. 31 After the adsorption of *CO 2 on ZnO to form a C−O bond, the electron pairs between the C−O bond would shift closer to the O atom side on the O-terminated (0001) plane compared with the (11̅ 00) plane owing to the electronegativity difference.…”
Section: Resultsmentioning
confidence: 99%
“…e interaction of ZnO with graphene is perhaps more of a dipole-dipole interaction rather than a direct charge transfer. It has been shown that both Znterminated polar surface of ZnO induces a dipole in the charge distribution of graphene [39]. While previous works describing photocatalysis of ZnO-graphene composites show that is comparatively e cient with this work, the kinetic rate could bene t more from a direct charge transfer rather than charge induction.…”
Section: Discussionmentioning
confidence: 57%